Thermodynamic Description of Ternary Fe-B-X Systems. Part 8: Fe-B-Mo, with Extension to Quaternary Fe-B-Cr-Mo System - Jyrki Miettinen; Ville-Valtteri Visuri; Timo Fabritius (Archives of Metallurgy and Materials, 2020)
Thermodynamic optimizations of the ternary Fe-B-Mo system and its binary sub-system B-Mo are presented. The Fe-B-Mo description is then extended to the quaternary Fe-B-Cr-Mo system by assessing the ternary B-Cr-Mo system. The thermodynamic descriptions of the other binaries (Fe-B, Fe-Cr, Fe-Mo, B-Cr, and Cr-Mo) and the other ternaries (Fe-B-Cr and Fe-Cr-Mo) are taken from earlier studies. In this study, the adjustable parameters of the B-Mo, Fe-B-Mo, and B-Cr-Mo systems were optimized using the experimental thermodynamic and the phase equilibrium data from the literature. The solution phases of the system (liquid, bcc and fcc) are described with the substitutional solution model, and most borides are treated as stoichiometric phases or semistoichiometric phases, using a simple two-sublattice model for the latter. The system’s intermetallic phases, Chi, Mu, R, and Sigma (not dissolving boron) as well as boride M3B2, based on a formulation of (Cr,Fe)(Cr,Fe,Mo)2(B)2, are described with a three-sublattice model. Reasonable agreement is obtained between the calculated and measured phase equilibria in all four systems: B-Mo; Fe-B-Mo; B-Cr-Mo; and Fe-B-Cr-Mo.